SYSTEMATIC LITERATURE REVIEW: DAMPAK AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN DI BURSA EFEK INDONESIA - Rahmania Dewi; Fira Fira; Amanda Dewi Fadillah; Aurora Choirunnisa; Endang Kartini Panggiarti (CV. Denasya Smart Publisher, 2026)
This study aims to comprehensively examine previous research findings regarding the impact of acquisitions on the financial performance of companies listed on the Indonesia Stock Exchange. In the business world, acquisitions are often used as a strategy to expand markets, improve operational efficiency, and strengthen competitive positioning. However, prior studies have shown inconsistent results, indicating the need for a more comprehensive literature review. By applying the Systematic Literature Review (SLR) method, this research analyzes ten journal articles published between 2021 and 2024. The findings reveal that some studies report improvements in efficiency and profitability after acquisitions, while others indicate a decline or no significant changes in financial performance. These variations are influenced by factors such as industry characteristics, financial conditions, and the effectiveness of post-acquisition integration. Overall, this study concludes that acquisitions do not necessarily lead to improved financial performance.